THE PARADIGM OF EUROPEANISM OF DARIIA VIKONSKA’S UKRAINIAN LITERATURE - Nabytovych, I. Y. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Dariia Vikonska was one of the brightest representatives of Ukrainian artistic and literary space of inerwar two decades of the ХХ century that was consistently engaged in the problems of Europeanization of Ukrainian culture and expressed the necessity of entry of this literature, art and culture into European cultural space in general. Dariia Vikonska tried to structure this cultural and artistic space, to define its peculiarities and modern features while seeking the place of Ukrainian culture in European space.